1987
DOI: 10.1021/jm00392a008
|View full text |Cite
|
Sign up to set email alerts
|

.gamma.-Aminobutyric acid esters. 3. Synthesis, brain uptake, and pharmacological properties of C-18 glyceryl lipid esters of GABA with varying degree of unsaturation

Abstract: A series of 14C-labeled and unlabeled di-gamma-aminobutyric acid esters of glyceryl lipids having zero to three double bonds (stearoyl, oleoyl, linoleoyl, and linolenoyl) were synthesized. Measurements of the octanol/water partition coefficients of the compounds showed an increase with decreasing number of double bonds (i.e., from linolenoyl to stearoyl). The brain-uptake index went up from 31.5 (linolenoyl) to 45.1 (stearoyl) and similarly the brain-penetration index went up from 15 (linolenoyl) to 28 (stearo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1988
1988
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Frey et al [21] reported that the convulsant thresholds were increased after oral administration of cetyl GABA. Jacob et al [22] reported that intraperitoneal injection of di-GABA lipid ester produced a considerable inhibition of general motor activity in mice. Meanwhile, Biswas et al [23] reported that high doses of intraperitoneal GABA injection altered the monoamine levels and their synthesis, similar to levels observed after intra-cerebroventricular injection.…”
Section: Discussionmentioning
confidence: 99%
“…Frey et al [21] reported that the convulsant thresholds were increased after oral administration of cetyl GABA. Jacob et al [22] reported that intraperitoneal injection of di-GABA lipid ester produced a considerable inhibition of general motor activity in mice. Meanwhile, Biswas et al [23] reported that high doses of intraperitoneal GABA injection altered the monoamine levels and their synthesis, similar to levels observed after intra-cerebroventricular injection.…”
Section: Discussionmentioning
confidence: 99%
“…The most common and straightforward strategy for creating lipidic prodrugs is the FA‐based prodrug approach involving conjugation of the drug moiety to the carboxyl end of the FA or to its modified ω ‐atom (Figure ). Conjugating the lipid's carboxyl end with a hydroxyl or amine group of the drug moiety results in a stable ester or amide bond and is the most common strategy to obtain these prodrugs. However, these prodrugs do not take advantage of the FA endogenous metabolic pathways, because a free carboxylate group is crucial for FA binding to albumin or for recognition by the FA‐binding transporter in the cell membrane; when this is the case, the FA can be modified in the ω‐ position, leaving the carboxylate group free …”
Section: Lipidic Prodrugs As a Mean For Enhancing Oral Drug Delivery:mentioning
confidence: 99%
“…A TG‐based prodrug approach utilizes the natural metabolic pathway of dietary lipids to improve some aspects of parent drug absorption and fate . Prodrugs using this approach have the potential to direct drugs to the lymphatic system, demonstrate improved oral delivery, and target specific organs, such as CNS and liver . In the intestinal lumen, TG undergoes selective hydrolysis of the sn‐1 and sn‐3 positioned FAs, leaving the sn‐2 monoglyceride to be absorbed, so naturally, a large number of TG‐based prodrugs have the drug moiety conjugated to the sn‐2 position .…”
Section: Lipidic Prodrugs As a Mean For Enhancing Oral Drug Delivery:mentioning
confidence: 99%
“…The results are presented in Table II and As seizures originate from the central nervous system, our attention was focused on the crossing of the blood-brain barrier by glycine and Nbenzyloxycarbonylglycine. The determination of the Brain Penetration Index (BPI) according to the method of Shashoua et al (10)(11)(12) was carried out. The BPI is defined as the following ratio : BPI = radioactivity in the brain x 100 radioactivity in the liver measured 5 min after the administration.…”
Section: The Synthesis Of N-benzyloxycarbonyl-[14c]-glycinementioning
confidence: 99%